2007
DOI: 10.1044/0161-1461(2007/007)
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of In-Service Education to Promote Emergent Literacy in Child Care Centers: A Feasibility Study

Abstract: A 2-day in-service education program resulted in short-term behavioral changes in educators' use of abstract language and print references. Suggestions for improving instruction include providing opportunities for classroom practice with feedback, modeling the use of strategies in classroom routines, and long-term mentoring of educators to promote retention of gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 28 publications
4
44
1
7
Order By: Relevance
“…However, despite widespread agreement about the need for this support of early childhood educators, little empirical research exists to guide policymakers and educators regarding the type, intensity, and duration of professional development that is most effective in helping early childhood educators acquire and implement background knowledge and mastery in instructional strategies that lead to improved child outcomes (Maxwell, Field, & Clifford, 2006;Snow, 2006). Although several previous studies have attempted to affect teachers' language and instructional behaviors within the classroom via professional development (Dickinson & Brady, 2006;Dickinson & Caswell, 2007;Girolametto, Weitzman, Lefebvre, & Greenberg, 2007;Landry, Swank, Smith, Assel, & Gunnewig, 2006;O'Connor, 1999) and have reported changes in classroom environments and some teacher behaviors (i.e., book reading, environmental print, and use of abstract language), these studies either did not measure or found no or only small changes in child outcomes.…”
Section: Professional Development In Early Childhood Educationmentioning
confidence: 93%
“…However, despite widespread agreement about the need for this support of early childhood educators, little empirical research exists to guide policymakers and educators regarding the type, intensity, and duration of professional development that is most effective in helping early childhood educators acquire and implement background knowledge and mastery in instructional strategies that lead to improved child outcomes (Maxwell, Field, & Clifford, 2006;Snow, 2006). Although several previous studies have attempted to affect teachers' language and instructional behaviors within the classroom via professional development (Dickinson & Brady, 2006;Dickinson & Caswell, 2007;Girolametto, Weitzman, Lefebvre, & Greenberg, 2007;Landry, Swank, Smith, Assel, & Gunnewig, 2006;O'Connor, 1999) and have reported changes in classroom environments and some teacher behaviors (i.e., book reading, environmental print, and use of abstract language), these studies either did not measure or found no or only small changes in child outcomes.…”
Section: Professional Development In Early Childhood Educationmentioning
confidence: 93%
“…environments that support reading and writing events and practices. Previous research (Connor, Morrison, & Slominski, 2006;Girolametto, Weitzman, Lefebvre, & Greenberg, 2007;Gustafsson & Mellgren, 2002;Neuman, 2007;Pianta, 2006;Saracho, 2004) shows that the quality of interaction in terms of attitudes, instructional support, and emotional tone among the preschool children, day-care attendants, and preschool teachers is significant for children's motivation in the early literacy-learning process.…”
Section: Introductionmentioning
confidence: 97%
“…Many of these studies focus on the effects of quality in child care arrangements, the quality of teachers, the effects of child care on children's behavior, or with the effects of child care on children's language development, among others (Belsky et al 2007;Girolametto et al 2007;Love et al 2003).…”
Section: Children In Child Carementioning
confidence: 99%